Analisis Harga Pokok Produksi untuk Menentukan Harga Jual Ayam Ternak Pada PT Semesta Mitra Sejahtera Sumatera Selatan - Muhammad Gilbran Elyus (PT. ALHAFI BERKAH INDONESIA, 2023)
Semesta Mitra Sejahtera South Sumatra is a company engaged in the field of chicken farming. Determining the cost of production has an important role for companies to help determine the selling price of a product, the company must first calculate the cost of production. The purpose of setting a price is to achieve company targets, gain profits from sales, increase and develop product production, and expand marketing targets. The decision to determine the cost of production is important for the company, because the decision to determine the cost of production affects the determination of the selling price that is informed.